2015
DOI: 10.1080/15389588.2014.969804
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Role of the Combination of Alcohol and Cannabis in South Australian Road Crashes

Abstract: The findings of the hospital data and the coroners' reports were consistent with each other in terms of providing confirmation that alcohol is still the drug associated with the greatest level of road trauma on South Australian roads. Furthermore, alcohol was also present in around half of the cannabis cases and, when present, tended to be present at very high levels. The results of this study emphasize that, although drug driving is clearly a problem, the most important form of impaired driving that needs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The results below highlight the prevalence of driving under the influence of drugs (DUID), legal charges, MVAs, FVAs, impairment analyses, road rage occurrence, and driver's perception of DUI or legal risk when under the influence of METH or MDMA. The 35 descriptive case series [11, 12, 41–73], provide supplemental information regarding cases that were involved in MVAs, SDUID or a similar violation, or charged with DUID or a similar violation. METH or MDMA exposure was determined mainly by subject interview and/or blood, urine, and oral fluid analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results below highlight the prevalence of driving under the influence of drugs (DUID), legal charges, MVAs, FVAs, impairment analyses, road rage occurrence, and driver's perception of DUI or legal risk when under the influence of METH or MDMA. The 35 descriptive case series [11, 12, 41–73], provide supplemental information regarding cases that were involved in MVAs, SDUID or a similar violation, or charged with DUID or a similar violation. METH or MDMA exposure was determined mainly by subject interview and/or blood, urine, and oral fluid analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation of observational studies includes challenges performing risk ratios of single substances (e.g., MDMA or METH), when subjects were positive for multiple substances in DUI, MVA, or FVA cases. Due to these limitations and few case‐control, case‐cohort, and studies with a similar design, we included 35 case series articles in effort to review more observational data [11, 12, 41–73]. Case series are generally accepted as having lower scientific rigor, and therefore, less emphasis was placed on them in the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A separate survey reported that among persons aged 18-29 years who drink alcohol, 15% report some simultaneous use of alcohol and marijuana (Subbaraman and Kerr 2015). The authors further use among injured drivers of all ages consistently find alcohol and marijuana to be among the most commonly detected substances, and the 2 are often found in combination (Baldock and Lindsay 2015;Brubacher et al 2016;Walsh et al 2005).…”
Section: Discussionmentioning
confidence: 97%